A Cost-Efficient RGB Laser-Based Visible Light Communication System by Incorporating Hybrid Wavelength and Polarization Division Multiplexing Schemes - Xiang-Peng, CAI (Frontiers in Physics, 2021)
Visible light communication (VLC) has been proven a promising technology to counter the limitations of radio frequency (RF) communication technology such as high interference and high latency issues. VLC offers high bandwidth as well as immunity to interference from other electromagnetic spectrums. Due to this features, VLC can be excellent solution for biomedical and healthcare applications for transmission of body sensor signals and other patient crucial patient information. In this work, highly efficient VLC system is designed to transmit six channels, with each one carrying 10 Gbps data, over 500m optical fiber link and 200cm VLC link. To make the VLC system cost effective, a simple and efficient on off key (OOK) (non-return to zero) is used as the encoding scheme. Moreover, to further enhance the capacity and bandwidth of the proposed VLC system, hybrid wavelength division multiplexing (WDM) and polarization division multiplexing (PDM) schemes are incorporated by using red, green and blue lasers. The reported results show the successful transmission of all channels (6 ×10Gbps) over 55m optical fiber and 200cm of VLC link.